Implementation of Total Quality Management (TQM) in Improving Product Quality in Manufacturing Companies - Fadli, Alim Dai (Generasi Sains Indonesia, 2024)
This paper will review the impact of the implementation of Total Quality Management (TQM) on the quality of the products, the engagement of the employees and customer satisfaction in a manufacturing company. A quasi-experimental study, further complemented by a pre-test/post-test procedure, has been implemented; TQM training was conducted with the experimental group whereas conventional training was used with the control group. The information was obtained by quality performance measures such as, defect rate, cycle time and overall equipment effectiveness (OEE) and surveys of employee perception and customer satisfaction. The comparison using statistical tools was done on paired t-test and independent t-test. The results show us statistically significant reduction of the defect rate, that was 4.5 percent to 2.0 percent and cycle time which was 25 minutes to 18 minutes in the case of the experimental group. At the same time, there was a significant boost in employee engagement and customer satisfaction with the sum total of the satisfaction level improving by a mark of 7.3 to 9.2. There was a significantly lower change in the control group. Overall, the results indicate that TQM initiatives delivered a significant effect on the quality of the products, staff involvement, and satisfaction with customers.